A balanced approach to understanding the shaping of human resource management in organisations - Paul Boselie (Management Revue, 2009)
There is a need for alternative theories to get a better understanding of human resource management (HRM), in particular with regard to the shaping of the employment relationship in organizations. This study examines how market, institutional and configurational factors affect HRM in a global financial services company using the strategic balance theory and Paauwe's model. Interview data and document analysis show the impact of critical incidents (e.g. a merger) and trends (e.g. a transition in Dutch industrial relations) on HRM.
Keywords: 650; HRM; strategic balance theory; context